SISTEM AGRIBISNIS AYAM KALKUN DI DESA SUKOHARJO KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Elvany Oktaviana; Dyah Aring Hepiana Lestari; Yaktiworo Indriani (Lampung University, 2016)
This study aims to know the supply system of production facilities, profits, added value of turkey products (satay, meatballs and nuggets), marketing mix and marketing channels in addition to supporting institutions of turkey farming in Sukoharjo Village. This study was conducted in Mitra Alam Turkey Farming House in Sukoharjo Village Pringsewu District. The data was collected in April 2015 - June 2015 using the case study method and was analyzedby descriptive quantitative analysis and Hayami method for the added value. The results showed that almost all of the production facilities were own production which were consisted of cages, seed and feed, while drugs were obtained by purchasing. The profit of turkey farming for one production or month was Rp29,702,167.00 with R/C in cash costs to 1.76 and R/C on total cost of 1.70. The added value of turkey products (satay, meatballs and nuggets) showed the highest added value product was turkey meatballs with ratio 86.78 percent. Marketing channel of turkey farming consisted of two channels, first from producers to consumer and, secondly from manufacturers to retailers then to consumers. Supporting institutions of turkey farming were consisted of farmer groups,information system and government policies.Key words: agribusiness system, breeding business, turkey